2020
DOI: 10.3390/ma13184169
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Electrical Polarity in Electrospinning and on the Mechanical and Structural Properties of As-Spun Fibers

Abstract: Electric field strength and polarity in electrospinning processes and their effect on process dynamics and the physical properties of as-spun fibers is studied. Using a solution of the neutral polymer such as poly(methyl methacrylate) (PMMA) we explored the electrospun jet motion issued from a Taylor cone. We focused on the straight jet section up to the incipient stage of the bending instability and on the radius of the disk of the fibers deposited on the collecting electrode. A new correlation formula using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 78 publications
2
37
0
Order By: Relevance
“…The decreased strength of porous compared to smooth fibers is also affected by the lower average fiber diameter that decreases the mechanical properties of PCL fibers [ 35 ] and high surface porosity [ 36 ], so the tested cross-sectional area is significantly lower which is not included in the calculation of the stress [ 37 ]. It demonstrates that the mechanical performance of electrospun fibers depends not only on fiber orientation but also on the interactions and adhesion forces between them [ 38 , 39 ] related to the changes in fibers morphologies or surface properties [ 40 , 41 ]. It was reported that the formation of the mechanical interlocking system strongly depends on surface properties and the presence of crevices, pores, roughness, and irregularities [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased strength of porous compared to smooth fibers is also affected by the lower average fiber diameter that decreases the mechanical properties of PCL fibers [ 35 ] and high surface porosity [ 36 ], so the tested cross-sectional area is significantly lower which is not included in the calculation of the stress [ 37 ]. It demonstrates that the mechanical performance of electrospun fibers depends not only on fiber orientation but also on the interactions and adhesion forces between them [ 38 , 39 ] related to the changes in fibers morphologies or surface properties [ 40 , 41 ]. It was reported that the formation of the mechanical interlocking system strongly depends on surface properties and the presence of crevices, pores, roughness, and irregularities [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The morphology and size of fibers prepared via electrospinning were affected by the polymer solution, environmental conditions, and applied electric field ( Krysiak et al, 2020 ; Szewczyk et al, 2020 ). It was followed by mechanical ( Ura et al, 2020 ) and surface properties ( Metwally et al, 2020 ). Therefore, PHBV-based scaffolds described in Suslu et al (2014) had significantly smaller diameters of 571 ± 160 nm compared to our study, however, similarly, they obtained increased fiber diameter with the addition of HA particles.…”
Section: Discussionmentioning
confidence: 99%
“…This method of scaffold fabrication allows the formation of fibrous nonwovens with morphology and architecture mimicking the fibrous structure of the extracellular matrix (ECM) which is crucial from the perspective of cells. In this process, a large number of various polymers and solvents can be used, both natural, such as gelatin, chitosan, collagen, etc., and synthetic, such as polycaprolactone (PCL) [21], polyvinylidene fluoride (PVDF) [22], poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) [23], poly(methyl methacrylate) (PMMA) [24], etc. By connecting different types of materials, hybrid materials can be developed, particularly as a mixture of synthetic and natural polymers.…”
Section: Conventional Te Scaffold Fabrication Techniques Vs 3d Printing Techniquesmentioning
confidence: 99%